Synthesis and characterisation of novel-activated carbon from waste biomass pine cone and its application in the removal of congo red dye from aqueous solution by adsorption - Dawood, Sara.; Sen, Tushar; Phan, Chi (Springer Netherlands, 2014)
This study was undertaken to synthesise a novel biomass-based chemically activated carbon from Australian pine cone and to investigate its effectiveness in the removal of anionic dye Congo red from aqueous solution. The effect of activation parameters such as the concentration of phosphoric acid and temperature were identified as the most efficient parameters for activation in the Congo red removal. The synthesised activated carbon was characterised by Fourier transform infrared and different physical properties, such as bulk density, CHNS analysis, carbon yield, particle size, zeta potential and Brunauer–Emmett–Teller surface area were also determined. Batch adsorption study showed that the amount of adsorption depends on various physicochemical process parameters, such as solution pH, dyeconcentration, temperature and adsorbent dose. It was observed that Langmuir maximum adsorption capacity was 500 mg/g at a pH of 3.5. Furthermore, pseudo-first order, pseudo-second-order, Elovich and intra-particle diffusion models were fitted to examine the adsorption kinetic and mechanism of adsorption. Equilibrium data were fitted with Langmuir, Freundlich and Tempkin adsorption isotherm models. Thermodynamic parameters such as delta G0, delta H0, and delta S0 were also calculated. Finally, a single-stage batch adsorber design for the Congo red adsorption onto activated carbon particles was presented based on the Freundlich isotherm model equation. These results indicated pine cone biomass is a good and cheap precursor for the production of an effective activated carbon adsorbent and alternative to commercial-activated carbon.